Simplikasi Kedudukan Anak Sumbang Dalam Penerimaan Harta Warisan Menurut Hukum Perdata - Ahmad L; Kairuddin Karim; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2023)
This research was carried out with the aim of knowing the legal status of a gifted child according to civil law and finding out the inheritance rights of a gifted child according to civil law. The type of method used is normative research. The research results show that the dissenting child cannot be recognized, thus the dissenting child does not have a civil relationship with his mother or father. As well as the inheritance rights of discordant children between Islamic law and the Civil Code have similarities and differences. The similarity is that both of them state that this child is an illegitimate child, so he does not have a family relationship with his father, which results in no mutual inheritance relationship between the two. An incestuous child cannot be assigned to his mother and father which causes the two of them to have no right to inherit each other, while in Islamic law a discordant child, even though this child may not be assigned to his father, this child is still assigned to his mother and the implication is that he can inherit and pass it on to his mother and father. his mother's family.